Financing hearing aids for patients with congenital deafness in Indonesia - Indra Zachreini; Jenny Bashiruddin; Semiramis Zizlavsky; Susyana Tamin; Harim Priyono; Ika Dwi Mayangsari; Widayat Alviandi; Natasha Supartono; Damayanti Soetjipto; Respati Ranakusuma; Heditya Damayanti; Dina Alia; Tengku Siti Hajar Haryuna; Juliandi Harahap; Nirza Warto; Hidayatul Fitria (PERHATI-KL, 2022)
ABSTRACTBackground: The appropriate management of patients with congenital deafness is installing hearing aids, either external hearing aids or implanted in the ear (cochlear implant), aiming to reduce the medical and social burden, besides improving the quality of life of the sufferers. Objective: To ascertain the cost of hearing aids in patients with congenital deafness, in the form of external hearing aids or cochlear implants. Method: A descriptive study with cross-sectional design using questionnaires through interviews. The sample size was 535 mothers whose children had congenital deafness at 24 hospitals with facilities for establishing a diagnosis of congenital deafness in 17 provinces in Indonesia. Result: Most respondents were aged 30-39 years (55%), occupations were housewives (71.8%), and education level was high school (52.5%). The type of hearing aid used mostly was external (92.7%), with 45.9% paid by personal expense. The surgically planted hearing aids in 22 children was mostly cochlear implants (95.5%), which were financed by the Indonesian Healthcare and Social Security Agency (BPJS) plus personal costs (50%). Discussion: This study found that the most common type of hearing aid used by children with hearing impairments was external hearing aids (92.7%) through independent financing (45.9%). Only 7.3% of patients chose surgery in hearing habilitation, and 95.5% were cochlear implants. The small percentage of surgery were due to the high-priced of cochlear implants, and the government did not cover all financial expenses. Conclusion: Most external hearing aids were paid independently-out-of-pocket, while cochlear implant surgeries were funded by BPJS, plus extra costs independently. ABSTRAKLatar belakang: Penatalaksanaan terbaik untuk penderita tuli kongenital adalah pemasangan alat bantu dengar (ABD), baik berupa ABD eksternal maupun ABD yang ditanam dalam telinga (implan koklea), dengan tujuan untuk mengurangi beban medis dan sosial, serta meningkatkan kualitas hidup penderita. Tujuan: Untuk mengetahui seberapa besar biaya pemasangan ABD pada penderita tuli kongenital, baik berupa ABD eksternal maupun implan koklea. Metode: Penelitian deskriptif dengan rancangan cross sectional study menggunakan kuesioner melalui wawancara. Besar sampel 535 ibu yang anaknya menderita tuli kongenital pada 24 rumah sakit yang memiliki fasilitas penegakkan diagnosis tuli kongenital di 17 provinsi di Indonesia. Hasil: Sebagian besar responden berusia 30-39 tahun (55%), pekerjaan terbanyak adalah ibu rumah tangga (71.8%), dan tingkat pendidikan SMA (52.5%). Jenis ABD yang terbanyak adalah ABD eksternal (92,7%) dengan pembiayaan secara mandiri 45,9%. Pemasangan ABD dengan tindakan operasi dilakukan pada 22 anak, yang terbanyak adalah implan koklea (95,5%) yang dibiayai oleh Badan Penyelenggara Jaminan Sosial (BPJS) ditambah dengan biaya sendiri (50%). Diskusi: Penelitian ini mendapati bahwa ABD yang terbanyak digunakan oleh anak dengan gangguan pendengaran adalah ABD eksternal (92,7%) dengan biaya mandiri (45,9%). Habilitasi pendengaran dengan tindakan operasi hanya dilakukan pada 7,3% pasien, berupa implantasi koklea 95,5%. Kecilnya persentase habilitasi bedah dikarenakan tingginya harga implant koklea, dan bantuan dari BPJS tidak meliputi keseluruhan biaya. Kesimpulan: Sebagian besar pembiayaan alat bantu dengar eksternal secara mandiri, sedangkan operasi implan koklea menggunakan biaya BPJS ditambah biaya sendiri.